The Shaping of Islam in Brunei Darussalam 1 - Müller, Dominik (Routledge Handbook of Islam in Southeast Asia, 2022)
This chapter discusses historical and contemporary developments of Islam in the sultanate of Brunei Darussalam, focusing on the transformations in the political position and social meanings of Islam in state and society. After a brief introduction of Islam in the pre-colonial period, the chapter outlines changes that occurred in the colonial era under British indirect rule, resulting in dramatic innovations pertaining to the administration and legalistic expression of Islam. New institutional and legal manifestations of Islam established during the colonial period structured later developments in the post-colonial era, beginning in 1984. The next section elucidates the rise of the post-colonial state’s national ideology called Melayu Islam Beraja, commonly referred to as ‘MIB’ and officially translated as ‘Malay Islamic Monarchy.' After a discussion of the contemporary ‘MIB State’ and government attempts of promoting the national ideology among its citizenry, the chapter turns to state attempts of supposedly ‘purifying’ Islamic practices and beliefs among the population, which have intensified since the 1990s, coinciding with significant sociocultural changes among the Malay majority population. Finally, the chapter offers concluding remarks on research gaps and potentials for future research.
CRIS-Team Scopus Importer:2022-10-28